Can we measure cognitive constructs consistently within and across cultures? Evidence from a test battery in Bangladesh, Ghana, and Tanzania. Issue 1 (2nd January 2018) - Holding, Penny; Anum, Adote; van de Vijver, Fons J. R.; Vokhiwa, Maclean; Bugase, Nancy; Hossen, Toffajjal; Makasi, Charles; Baiden, Frank; Kimbute, Omari; Bangre, Oscar; Hasan, Rafiqul; Nanga, Khadija; et al.
ABSTRACT: We developed a test battery for use among children in Bangladesh, Ghana, and Tanzania, assessing general intelligence, executive functioning, and school achievement. The instruments were drawn from previously published materials and tests. The instruments were adapted and translated in a systematic way to meet the needs of the three assessment contexts. The instruments were administered by a total of 43 trained assessors to 786 children in Bangladesh, Ghana, and Tanzania with a mean age of about 13 years (range: 7–18 years). The battery provides a psychometrically solid basis for evaluating intervention studies in multiple settings. Within-group variation was adequate in each group. The expected positive correlations between test performance and age were found and reliability indices yielded adequate values. A confirmatory factor analysis (not including the literacy and numeracy tests) showed a good fit for a model, merging the intelligence and executive tests in a single factor labeled general intelligence. Measurement weights invariance was found, supporting conceptual equivalence across the three country groups, but not supporting full score comparability across the three countries.